A new species of fishing spider Dolomedes Latreille 1804 (Araneae Pisauridae) from the Philippines - Barrion, Alberto T. (Asia life sciences :the international journal of life sciences., 1995)
"Dolomedes mindigoetmopasi n. sp., the second species of the genus known from Luzon Island, Philippines is described and illustrated."